12.3: Research on Reducing H: P Value of Lensless Direct‐lit Backlight Module. (26th August 2021) - Li, Fulin; Zong, Zhihao; Zhang, Nannan; Mu, Linjia; Liu, Xiaojie
Abstract : The direct‐lit mini LED backlight LCD module can utilize ultra‐fine local dimming technology. This approach can realize not only the thinning of backlight unit, but also more refined dynamic control, improving the dynamic contrast of liquid crystal display. As displays continue to develop toward thinness, the number of required LED chips has increased significantly, causing cost and energy consumption issues. The industry usually uses H: P value (OD/LED pitch) to describe the relationship between the cost and thickness of the backlight module. In this work, mini LED technology was researched and applied. Firstly, a blue light angular bidirectional optical film was applied. By controlling the thickness and refractive index of the multilayer film, an effect of reflecting a small angle and transmitting a large angle of blue light was realized, which increased the irradiation range of a single LED. In this way, the H: P value can be reduced from 0.6 to 0.3. Then top shielding structure of the secondary package was used to expand the light‐emitting angle of the mini LED chips, which reduced the H: P value from 0.64 to 0.48. Finally, the two schemes were combined to bring the H: P value to 0.24. This design reduced the thickness of the module under low‐cost conditions and reached the most advanced level in the industry.